MITIGASI BENCANA ABRASI DI KECAMATAN TUGU OLEH PEMERINTAH KOTA SEMARANG - Muhamad Dwi Septiawan; Ida Hayu Dwimawanti; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Coastal areas in Indonesia are very vulnerable to a disaster. One of the threats to coastal areas is abrasion. Problems regarding abrasion in recent years tend to increase in various coastal areas, especially those that occur in coastal areas in the Tugu sub-district. However, the implementation of abrasion disaster mitigation that has been carried out has not been able to run optimally. This study aims to analyze the abrasion disaster mitigation in the Tugu subdistrict and the supporting and inhibiting factors. The research method used is descriptive qualitative research method. Data were collected through interview techniques for primary data, with 4 informants who were determined using snowball sampling techniques and accidental sampling techniques. Then documentation techniques for secondary data. The results of the study show that the implementation of abrasion disaster mitigation in the Tugu sub-district is carried out by structural and non-structural mitigation through environmental conservation, regulation of building layouts and infrastructure development, and outreach and education. In addition, the implementation of abrasion disaster mitigation is still not optimal, this is because the coordination between actors has not gone smoothly, the mindset of the people who still do not care, and the limited available budget. The researcher recommends increasing coordination between actors regarding the implementation of regional spatial planning so that an integrated implementation of abrasion disaster mitigation is created.